1999
DOI: 10.1046/j.1365-2842.1999.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biting forces in different age and sex groups: a study of biting efficiency with mobile and non‐mobile teeth

Abstract: This study aimed (1) to investigate the influences of sex, age and number of teeth on biting ability through a descriptive survey, and (2) to compare the biting ability between the subjects with and without mobile teeth in a case-control study. A total of 687 subjects cooperated in the descriptive survey. Each subject bit on a pressure detecting sheet with their maximum biting force. Three indices of biting ability: biting pressure (MPa), biting force (N) and occlusal contact area (mm2) were calculated from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
90
2
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 10 publications
12
90
2
4
Order By: Relevance
“…14, 23 We found the bite force stronger in men (512 N) than in women (443 N), echoing the findings from previous studies. 23,24 This might be a result of difference in muscle strength.…”
Section: Discussionsupporting
confidence: 88%
“…14, 23 We found the bite force stronger in men (512 N) than in women (443 N), echoing the findings from previous studies. 23,24 This might be a result of difference in muscle strength.…”
Section: Discussionsupporting
confidence: 88%
“…The biting force correlates with the number of teeth and functional pairs of teeth 14 . Thirteen of our 17 patients were fully dentulous or showed only one missing tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported bite force as a clinical indicator of masticatory performance. This parameter is correlated with craniofacial morphology (Tsunori et al), gender (Tate et al, 1994) age (Klitgaard et al, 1990) temporomandibular disorders (TMD) (Pizolato & Gaviao, 2007), and also with status, number and tooth mobility (Miyaura et al, 1999).…”
Section: Introductionmentioning
confidence: 99%